Pengaruh Kadar Air terhadap Beberapa Sifat Fisik Biji Lada Putih - Andi Muhammad Akram Mukhlis; Edy Hartulistiyoso; Yohanes Aris Purwanto (agriTECH, 2017)
The physical properties of seed are required in designing an  apparatus for handling, separation, drying, storage, and processing. The physical properties of white pepper seeds were  determined as a function of moisture content in the range of  15,40 - 64,80 % dry basis (d.b.). The average height, length and width at a moisture content condition of 15,40 % (d.b.) were 4,11 ± 0,27 mm; 4,35 ± 0,34 mm and 4,35 ± 0,35 mm, respectively.  In the range of moisture content 15,40 - 64,80 % (d.b.), the  results of this study showed an increase linearly of the third axial  dimension, the average diameter, the roundness from 0,969 to 0,977, the volume from 39,50 to 67,34 mm3, the surface area  from 55,87 to 79,92mm2 and the thousand seed mass from  52,47 to 75,63 g. Bulk density and true density has a polynomial  correlation with changes in moisture content.The porosity  decreased from 45,01 % to 44,88 % with an increase in the  moisture content range of 15,40 - 64,80 % (d.b.). ABSTRAKSifat fisik biji-bijian diperlukan dalam merancang suatu peralatan  untuk penanganan, pemisahan, pengeringan, penyimpanan dan  pengolahannya. Sifat fisik biji lada putih ditentukan sebagai  fungsi kadar air pada rentang 15,40 - 64,80 % basis kering  (b.k.). Tinggi, panjang dan lebar rata-rata pada kondisi kadar air  15,40 % (b.k.) adalah 4,11 ± 0,27 mm; 4,35 ± 0,34 mm dan  4,35 ± 0,35 mm berturut-turut. Pada rentang kadar air 15,40 -  64,80 % b.k., hasil penelitian ini menunjukkan peningkatan  secara linear pada ketiga dimensi aksial, diameter rata-rata,  kebulatan dari 0,969 hingga 0,977, volume dari 39,50 hingga  67,34 mm3, luas permukaan dari 55,87 hingga 79,92 mm2 dan  massa seribu biji dari 52,47 hingga 75,63 g. Bulk density dan true density memiliki hubungan polinomial dengan perubahan kadar  air biji. Porositas menurun dari 45,01 % hingga 44,88 % dengan  peningkatan kadar air pada rentang 15,40 - 64,80 % (b.k.).